The ups and downs of drugs - Elgin, Kathleen 1923-; Osterritter, John Ferdinand 1923- (Manila National Book Store, 1972)
Discusses the beneficial and dangerous aspects of a variety of drugs including stimulants, depressants, narcotics, and hallucinogens.
Keywords: Drugs -- Juvenile literature; Drug abuse -- Juvenile literature; Drug abuse; Drugs